Peran Dinas Sosial Dalam Penanganan Tuna Wisma Di Kota Padang - Indah Flecia Putri; Clarissa Amanda; Nanda Novirza; Nurfaiza Nurfaiza; Olivia Dwi Ruselda (Universitas Palangka Raya, 2023)
The high number of homeless people in the city of Padang is caused by economic and cultural factors in the community. The most important thing that must be considered by social services is the guidance of the homeless. Because at certain times the homeless population increases, such as on holidays, religious holidays, or in recreation centers. However, if due to the family's unfavorable economic conditions, it becomes a factor for children to go to the streets to work to help their parents. Homeless people are a city community, their presence is closely related to the environmental conditions of the children's community. Homeless people who have been netted cannot be sure that they will not take to the streets again. This is due to various reasons, such as economic needs that are still not fulfilled and there are no other activities that can generate money, forcing the child to take to the streets again. One of the programs for dealing with homeless people at the Social Service is working with Satpol PP to screen homeless people. So the guidance for families that must be carried out by social services is by empowering the family economy which creates independence, so that finally with the various coaching programs provided, both to the child and to his family it is hoped that they will not return to the streets again. The purpose of this study was to find out how the role of the Padang City Social Service in dealing with existing homeless people. Implementation of this research using descriptive qualitative method. The results of this study found how the role of the Padang City Social Service in dealing with the existing Homeless, as well as how the efforts were made and the inhibiting factors in handling the Homeless.